MENERAPKAN PEMBELAJARAN KONTEKSTUAL BERBASIS KEARIFAN LOKAL DALAM PENDIDIKAN MATEMATIKA: MEMBANGUN IDENTITAS BUDAYA DI ERA DIGITAL - Nazwa, Nadhilah; Surbakti, Desi Sri Kelengna; Gultom, Anggita Uli Angel; Mailani, Elvi (Jurnal Merah Putih Sekolah Dasar, 2025)
This study was motivated by the limited research on the integration of local wisdom in mathematics learning, despite its significant impact in supporting meaningful learning and strengthening students' cultural identity. This study aims to explore and analyze the application of local wisdom-based contextual learning methods in mathematics education, as well as their impact on learning outcomes and the strengthening of students' cultural identity in the digital age. This study adopts a qualitative design with a literature review approach, where data sources are obtained from relevant scientific journals, books, and research reports. The findings show that contextual learning based on local wisdom is effective in bridging abstract mathematical concepts with students' concrete experiences, increasing learning motivation, and strengthening cultural identity awareness. This study concludes that this method has significant pedagogical and cultural potential and contributes to the development of contextual learning and ethnomathematics theory. This study also identifies opportunities for future research on the effectiveness of this approach in various cultural contexts and the use of digital platforms in its implementation.